Ansiedade e estresse em estudantes do curso de graduação em odontologia, fatores relacionados e suas repercussões - Danielle Beatriz de Paula Pires (2024)
Anxiety and stress are natural conditions, as they are part of the physiological response to threatening and dangerous situations. However, when there is a disproportionate response, with harm to the individual, anxiety and stress are considered pathological, resulting in different consequences. There is a clear need for further studies in this area, with early identification of anxiety and stress among dentistry graduates and associated factors. The general objective of this dissertation is to evaluate anxiety and stress in undergraduate dentistry students, the related factors and their repercussions and is divided into two studies. Study 1: Systematic literature review. Search carried out in December 2022, in the databases PubMed, Web of Science, Virtual Health Library, Cochrane, Embase and Scopus, considering the following question: “Anxiety and/or stress impact the quality of life of Dentistry students?”. And Study 2: quantitative, analytical and cross-sectional, with the objective of evaluating associations of anxiety and stress with factors of basic human needs (psychobiological, psychosocial and psychospiritual) in undergraduate Dentistry students at the Federal University of Minas Gerais (UFMG). 354 students participated, from the first to the tenth period, corresponding to 46.6% of the total enrolled in 2023. Regarding the results of Study 1, five studies were included in the review, four studies evaluated anxiety and one study evaluated stress, all of which transverse type. Although there are no studies evaluating the long-term impact, an association between anxiety and quality of life in undergraduate Dentistry students was identified. However, the same was not observed for stress. While in Study 2, variables associated with moderate/severe anxiety were: report of feeling like abandoning the course [3.55 (2.04-6.18); p<0.001]; self-rated academic performance as bad/very bad/neither bad nor good [2.07 (1.18-3.64); p<0.011] and not using integrative and complementary health practices [0.56 (0.36-0.87); 0.011]; and associated with above-average stress scores among FAOUFMG students were the following variables: gender [3.37 (1.78-6.38); p<0.001]; report of feeling like abandoning the course [2.46 (1.42-4.25); p<0.001]; self-assessment of academic performance as Poor/Very poor/Neither bad nor good [2.34 (1.34-4.10); p<0.003]. It is concluded, based on studies 1 and 2, that there is an association between anxiety and quality of life, proven through cross-sectional studies in the scientific literature, and that the variables related to the course (feeling of dropping out and self assessment of poor performance) highlighted associated with stress and anxiety among FAOUFMG students. Therefore, there is a need for actions aimed at promoting a welcoming environment that is attentive to the emotional, psychological, social, personal and academic issues that affect Dentistry students.